The Phenomenon of «Islamic State» - A. V. Fedorchenko; A. V. Krylov (Vestnik MGIMO-Universiteta, 2015)
On the first day of the holy month of Ramadan July 29,2014, jihadist organization "Islamic State" (IG), formerly known as "Islamic State of Iraq and the Levant" (ISIS), announced the creation of a "caliphate" in the areas controlled by its militants in Iraq and Syria. Using the weakness of state power and poignancy of inter-ethnic, inter-tribal conflicts, the leaders of the ISIS were able to multiply the number of its supporters and increase their influence. The crisis of "secular ideologies" (primarily Western liberalism and communism), greatly contributed to the success of "Islamic boom", including the creation of the ISIS. It prompted broad appeal to the Muslim masses on the ideological basis closer to them in spirit, mentality, purely religious values. The ISIS is funded better than any other extremist group before it. At least five sources of replenishment of its finances can be named. Current goals ofjihadists include the use of a power vacuum, bringing chaos in the various territories in the Muslim world, and prepare the ground for the transition to the ultimate goal of the program, namely the re-establishment, as it is declared, of the powerful theocratic state - the Caliphate, in the likeness of that which existed in Middle Ages, during the victorious Muslim conquests in the VII-IX centuries. The effectiveness of the fight against the ISIS depends on a combination of political, military, economic and social measures. Furthermore, it should be coordinated internationally. International coordination of anti-terrorist activities of Russia with the West and the East should bring positive results.